Cost effectiveness of high-sensitivity troponin compared to conventional troponin among patients presenting with undifferentiated chest pain: A trial based analysis. (1st July 2017) - Kaambwa, Billingsley; Ratcliffe, Julie; Horsfall, Matthew; Astley, Carolyn; Karnon, Jonathan; Coates, Penelope; Arstall, Margaret; Zeitz, Christopher; Worthley, Matthew; Beltrame, John; Chew, Derek P.
Abstract: Background: Patients with low and intermediate risk chest pain features comprise the greatest proportion presenting to emergency services for evaluation of suspected acute coronary syndromes (ACS). The efficient and timely identification of patients with these features remains a major challenge within clinical practice. Troponin assays are increasingly being used for the determination of risk among patients presenting with chest pain potentially facilitating more appropriate care. To date, no economic evaluation comparing high-sensitivity troponin T (hs-TnT) reporting to standard troponin T (c-TnT) reporting in the routine management of suspected ACS and based on longer-term clinical outcomes has been conducted. Methods and results: An economic evaluation was conducted with 1937 participants randomized to either hs-TnT ( n  = 973) or c-TnT ( n  = 964) with 12 month follow-up. The primary outcome measure was the number of cumulative combined outcomes of all-cause mortality and new or recurrent ACS avoided. Mean per participant Australian Medicare costs were higher in the hs-TnT arm compared to the c-TnT arm (by $1285/patient). Mean total adverse clinical outcomes avoided were higher in the hs-TnT arm (by 0.0120/patient) resulting in an incremental cost-effectiveness ratio (ICER) of $108, 552/adverse clinical outcome avoided. An ICER of $49, 030/adverse clinical outcome avoided was obtained when the analysis was restricted to patients below the threshold of normal Troponin testing (actual c-TnT levels < 30 ng/L). Conclusions: hs-TnT reporting leads to fewer adverse clinical events but at a high ICER. For the routine implementation of hs-TnT to be more cost-effective, substantial changes in clinical practice will be required. Clinical trial registration: Australian New Zealand Clinical Trials Registry (ACTRN12614000189628). https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=365726